Effect of Repaglinid on Ovariectomy Induced Bone Loss in Rats: Comparison with 17β-Estradiol (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the effect of repaglinide (RPG), anti-diabetic drug used commonly diabetic patients, on bone loss ovariectomized (OVX) rats”.
Keywords: 17β-Estradiol; Repaglinide; Ovariectomy; Bone Mineral Content; Bone Mineral Density.